Does phosphogypsum addition affect phosphate rock dissolution in acid soils? - Moussa Bouray; Moussa Bouray; Jim Moir; Khalil El Mejahed; Khalil El Mejahed; Redouane Choukr-Allah; Redouane Choukr-Allah; Mohamed El Gharous; Mohamed El Gharous (Frontiers in Environmental Science, 2023)
The direct application of phosphate rock (PR) has been found suitable for acidic soils. Still, efforts are needed to improve its reactivity to match grassland P demand. This research aimed to investigate changes in the dissolution of two Moroccan sedimentary PRs (Ben Guerir and Khouribga) in response to four rates of phosphogypsum (PG)—a by-product of the phosphate fertilizer industry. We conducted a 60-day incubation study using two acid soils from New Zealand. The soils were treated with PRs at 100 mgP kg−1 of soil either alone or combined with PG, which was applied at 0, 1, 3 and 9 t ha−1 (approximately the equivalent of 0, 0.9, 2.7, and 8.1 g of PG kg−1 of soil, respectively). The dissolution rates were determined from the differences in residual calcium (Ca) extracted with 1 M HCl. Soil pH, Olsen P, exchangeable aluminium (Al) and Ca and Ca saturation were analyzed at the end of the experiment. Phosphate rocks and PG’s physicochemical properties were characterized. Phosphogypsum addition increased Olsen P by 34% and 59% at 9 t ha−1 compared to 0 t ha−1 in Molesworth and Lindis Peaks soils, respectively. However, PG did not affect the dissolution of PRs in the different of soil types. Khouribga PR was more reactive than Ben Guerir PR, especially in the Molesworth soil where soil pH and base saturation were lower and P retention was higher compared to Lindis Peaks soil. Particle size distribution was the key factor that contributed to the observed greater reactivity of the Khouribga PR. Both PRs showed dissolution rates >50%, suggesting their suitability for direct application on acid soils. Being an important source of sulphur and some P, PG if combined with PR, can promote and complement PR’s direct use as fertilizer on acid soils. Moreover, the development of new fertilizer products by combining these two materials should be encouraged.